2009
DOI: 10.3200/bmed.34.4.125-132
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Relation to Posttraumatic Stress Disorder and Depression in the US National Comorbidity Survey

Abstract: The clinical literature increasingly indicates that cardiovascular risk factors and cardiovascular disease (CVD) are more common among individuals with posttraumatic stress disorder (PTSD). Depression also poses a risk for CVD and is often comorbid with PTSD. Research to date has not established whether PTSD is associated with additional CVD risk beyond the risks associated with comorbid depression. The authors examined relationships of lifetime PTSD and depression with high blood pressure in data from the US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
100
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 35 publications
7
100
2
Order By: Relevance
“…PTSD patients have significantly higher diastolic blood pressure compared with patients afflicted by other psychiatric disorders [89]. Data from the US National Comorbidity Survey suggest PTSD to be related to hypertension independently of depression [177]. …”
Section: Cardiovascular Disease and Mortalitymentioning
confidence: 99%
“…PTSD patients have significantly higher diastolic blood pressure compared with patients afflicted by other psychiatric disorders [89]. Data from the US National Comorbidity Survey suggest PTSD to be related to hypertension independently of depression [177]. …”
Section: Cardiovascular Disease and Mortalitymentioning
confidence: 99%
“…Data from the U.S. National Comorbidity Survey showed that people with PTSD had a 2.9-fold greater risk for developing hypertension (51). In a sample of more than 300,000 veterans of the Iraq and Afghanistan wars, those with PTSD had a 59% higher chance of developing hypertension compared with those without PTSD (19).…”
mentioning
confidence: 99%
“…Moreover, in the Framingham Coronary Heart Disease study, patients with PTSD were found to have increased Framingham risk scores for CVD (40). To date, there have been six PTSD-CVD prospective studies completed, following participants from 1 to 30 years, which have demonstrated consistent associations between PTSD and CVD after adjusting for demographic, clinical, and psychosocial factors, including depression (15,44,57,58,89,96).There are multiple risk factors (stroke, hypertension, atherosclerosis, and obesity metabolic syndrome) for the development of CVD, and increases in the incidence of these risk factors are often associated with PTSD (1,22,30,51,111 In a 14-year prospective study of more than 1,900 patients, men had an increased risk for both nonfatal myocardial infarction and fatal coronary heart disease with every SD increase in symptom level; similarly, women with five or more PTSD symptoms had over three times the risk of incidence of CVD (57, 58). It is also worth noting that clinically significant PTSD symptoms can be induced by cardiovascular related events, and these individuals are more likely to have recurrent major adverse coronary events (24, 59).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important, because both hypertension and hyperlipidemia have been associated with PTSD. 19,20 Although PTSD did not explain the entire impact of combat on cardiovascular risk, it does appear to have at least some mediating role. Several modalities for PTSD treatment have been shown to reduce symptoms.…”
Section: Circulationmentioning
confidence: 99%